RETRACTED: Waqas et al. Gyrotactic Motile Microorganisms Impact on Pseudoplastic Nanofluid Flow over a Moving Riga Surface with Exponential Heat Flux. Crystals 2022, 12, 1308 - Hassan Waqas; Mowffaq Oreijah; Kamel Guedri; Sami Ullah Khan; Song Yang; Sumeira Yasmin; Muhammad Ijaz Khan; Omar T. Bafakeeh; El Sayed Mohamed Tag-ElDin; Ahmed M. Galal (Crystals)
The Journal retracts the article entitled “Gyrotactic Motile Microorganisms Impact on Pseudoplastic Nanofluid Flow over a Moving Riga Surface with Exponential Heat Flux” [...]